Upaya pengendalian dan pencegahan penyakit hipertensi pada keluarga - Mohammad Haekal; Muhammad Daffa Alifio; Muhammad Syahrul Zain; Nizar Ahmad; Rizky Perdana Susanto (Yayasan Inspirasi El Burhani, 2021)
Introduction: Hypertension is defined as an increase in blood pressure exceeding 140/90 mmHg on two examinations within 5 minutes in an inactive/quiet state. Long-term increase in blood pressure can lead to complications if not treated early. Objective: The elderly are more at risk or tend to be susceptible to various degenerative diseases when compared to young people. One of the symptoms of hypertension is a headache. Headache is defined as an unpleasant feeling in the entire head area from the lower border of the chin to the back of the head (occipital area and part of the nape of the neck). Method: The main factors of this disease are genetics, behavior and lifestyle. Lack of awareness about the management of hypertension is a major cause of stroke complications. Result: Knowledge about hypertension is important so that people, especially the elderly, understand the signs and symptoms of hypertension from an early age. Conclusion: Therefore, it is very important to promote health promotion to the public regarding hypertension, so that the elderly understand the dangers of hypertension and to increase knowledge for the elderly about hypertension, so that people know how to prevent and control hypertension.